Haptic Distance Ratio Estimation: The Geometry of Space Within the Hands. (December 2018) - Norman, J. Farley; Wheeler, Sydney P.; Pedersen, Lauren E.; Dowell, Catherine J.
In the current study of haptic distance perception, 20 younger (median age: 22 years) and 20 older adults (median age: 72 years) used active touch to estimate distance ratios(one length relative to another). Nine tactile stimuli were created from wooden dowels; each consisted of two perpendicular dowels. The stimulus distance ratios ranged from 1.0 to 5.0. Each participant used both hands (without vision) to actively explore (30 s) a single stimulus object on every trial. The task was to numerically estimate the distance ratio. Overall, the participants' judgments were precise; the overall magnitude of the Pearson r correlation coefficient was 0.943 and did not differ for younger and older adults. While the participants' judgments were precise, they were not completely accurate: The average slope (of the relationship between actual and judged distance ratios) for all participants was significantly greater than 1.0 (1.15). Surprisingly, differences in manual dexterity had no apparent effect on distance ratio estimates. Older adults apparently retain an excellent ability to perceive distances using their sense of touch. Our results also demonstrate that the geometry of haptic space (at the scale of the hand) is approximately Euclidean in nature (and certainly not merely topological, projective, or affine).